Judges and Legislators : Toward Institutional Comity - Judges and Legislators: Toward Institutional Comity (The Brookings Institution, 1988)
The judiciary and congress not only do not communicate on their most basic concerns: They do not know how they may property do so, "writers Frank M. Coffin, a federal appeals court judge and former representative, in Judges and legalslator "The condition is that of a chronic, debilating fever.